Advanced Machine Learning and Statistical Modelling for the Assessment of Water Quality and Trophic Dynamics in the Upper and Middle Ganga River Basin - Jeetendra Kumar; Basanta Kumar Das; Asha T. Langde; Absar Alam; Ajoy Saha; Shashi Bhusan; Vikas Kumar; Rayees Ahmad Bhatt; Simanku Borah; Nitesh Kumar Sharma (Water, Air, & Soil Pollution, 2026)

Phytoplankton functional groups regulated by hydrological parameters in cascading reservoirs of the subtropical Ganga River, India - Jeetendra Kumar; Basanta Kumar Das; Asha Taterao Landge; Absar Alam; Ajoy Saha; Shashi Bhusan; Sandeep Kumar Mishra; Simanku Borah (Aquatic Ecology, 2025)

Water quality assessment of river Ganga, India using water quality index and multivariate statistical techniques - Sandeep Kumar Mishra; Vikas Kumar; Jeetendra Kumar; Dharm Nath Jha; Absar Alam; Venkatesh Ramrao Thakur; Sushil kumar Verma; Upendra Singh; Basanta Kumar Das (Environmental Monitoring and Assessment, 2025)

Fate and Effects of Heavy Metals in Fishes: Antioxidant Defense System, miRNA/Gene Expression Response, and Histopathological Reproductive Manifestations - Rayees Ahmad Bhat; Absar Alam; Dharm Nath Jha; Vikas Kumar; Jeetendra Kumar; Venkatesh Ramrao Thakur; Basanta Kumar Das (Biological Trace Element Research, 2024)

Water Quality Assessment, Possible Pollution Source Identification from Anthropogenically Stressed River Yamuna, India using Hydrochemical, Water Quality Indices and Multivariate Statistics Analysis - Vikas Kumar; Absar Alam; Jeetendra Kumar; Venkatesh Ramrao Thakur; Vijay Kumar; Saket K. Srivastava; Dharm Nath Jha; Basanta Kumar Das (Water, Air, & Soil Pollution, 2024)

Ecological and human health risk from exposure to metal contaminated sediments in a subtropical river affected by anthropogenic activities: A case study from river Yamuna - Vikas Kumar; Jeetendra Kumar; Absar Alam; Venkatesh Ramrao Thakur; Vijay Kumar; Saket Kumar Srivastava; Tania Kayal; Dharm Nath Jha; Basanta Kumar Das (Marine Pollution Bulletin, 2024)

Genetic characterization of minor carp (Labeo gonius) from Indian rivers revealed through mitochondrial ATPase 6/8 and D-loop region analysis: implications for conservation and management - Suvra Roy; Bijay Kumar Behera; Ramya V. L.; Ajay Kumar Rout; Vikash Kumar; Pranay Kumar Parida; Asim Kumar Jana; Pronob Das; Dharmendra Kumar Meena; Dibakar Bhakta; Absar Alam; Basanta Kumar Das; et al. (Frontiers in Marine Science, 2024)
India is the habitat of many freshwater fish species that make a significant contribution to endemism. However, the native species population is declining at a very fast rate due to pollution, habitat loss or degradation, new species introduction, hydrologic alterations, and overfishing. The minor carp, Labeo gonius , is one of the important fish species in the Indian river systems and holds enormous potential in culture fisheries. Therefore, the precise status of population structure is a prerequisite for the management of the species. In the present study, we assessed the potential of mtDNA ATPase 6/8 and D-loop regions as markers to determine the genetic diversity and phylogeography of L. gonius from Indian rivers. We have selected five major Indian rivers for investigation which could represent geographically distant populations of the studied fish. A total of 210 ATPase 6/8 sequences (842 bp) and 203 D-loop region sequences (683 bp) of L. gonius from the five major Indian rivers were submitted to NCBI. Results revealed that ATPase 6/8 has 17 haplotypes and 70 polymorphic sites with an overall haplotype diversity of 0.560 ± 0.036 and nucleotide diversity of 0.00347 ± 0.00. Furthermore, D-loop analysis revealed 58 haplotypes, 67 polymorphic sites, 0.954 ± 0.006 overall haplotype diversity, and 0.01914 ± 0.00 nucleotide diversity. The hierarchical AMOVA analysis indicated that a high proportion of the genetic variation (76.46% and 70.22% for the D-loop and ATPase 6/8 regions, respectively) was attributed to among-population variation under gene pool-1 (considering all the stocks from Ganga, Brahmaputra, Teesta, Narmada, and Mahanadi as a single pool). Furthermore, in gene pool-2, samples were divided into two groups: group 1 (Himalayan rivers)—Ganga, Brahmaputra, and Teesta; and group 2 (peninsular rivers)—Narmada and Mahanadi. Genetic variations in the D-loop and ATPase 6/8 regions were found among populations within groups at 70.65% and 53.48%, respectively. Haplotype network analysis revealed that there were significant differences in distributions and frequencies. The observed unique haplotypes might be useful for differentiating the stocks. In brief, the present study suggested that the D-loop and ATPase 6/8 regions are potential markers and represent a significant contribution to the genetic characterization of the minor carp L. gonius from major Indian rivers. Moreover, the L. gonius population along the east coast especially in the Himalayan rivers (Ganga, Brahmaputra, and Teesta river basin) is found to be genetically more diverse. The results would provide a scientific basis for the assessment of fisheries resources and management of this important species.

Fishery, growth, mortality, and stock assessment of endangered Tor putitora from Tehri dam reservoir, Uttarakhand, Himalayan foothills of India in relation to environmental variables - Dibakar Bhakta; Basanta Kumar Das; Upendra Singh; Archisman Ray; Canciyal Johnson; Venkatesh Ramrao Thakur; Sandeep Kumar Mishra; Sushil Kumar Verma; Absar Alam; Dharam Nath Jha (Environmental Monitoring and Assessment, 2023)

Influence of barrages on hydrological parameters and functional groups of phytoplankton of a subtropical river Ganga, India - Jeetendra Kumar; Absar Alam; Simanku Borah; Pranab Gogoi; Basanta Kumar Das (Environmental Science and Pollution Research, 2023)

Impact of barrages on assemblage pattern of phytoplankton in tropical river Ganga, India - Jeetendra Kumar; Absar Alam; Dharm Nath Jha; Pranab Gogoi; Simanku Borah; Basanta Kumar Das (Environmental Monitoring and Assessment, 2022)

Assessing assemblage pattern, health status and environmental drivers of macrobenthic invertebrate community structure for sustainable management in a tropical tributary of River Ganga, India - Shyamal Chandra Sukla Das; Dharm Nath Jha; Absar Alam; Simanku Borah; Vijay Kumar; Kalpana Srivastava; Venkatesh Ramrao Thakur; Amiya Kumar Sahoo; Basanta Kumar Das (Sustainable Water Resources Management, 2022)

The first report on food and feeding habits of yellowtail mullet, Minimugil cascasia (Hamilton, 1822), of the tropical River Ganga, India - Jeetendra Kumar; Absar Alam; Basanta Kumar Das (Environmental Biology of Fishes, 2022)

Evaluating the effectiveness of fingerling stocking and ecological perspectives in enhancing fish harvest in a large tropical reservoir of Northern India - Absar Alam; Jeetendra Kumar; Uttam Kumar Sarkar; Dharm Nath Jha; Saket Kumar Srivastava; Vijay Kumar; Basanta Kumar Das (Environment, Development and Sustainability, 2021)

Assessing the phytoplankton community and diversity in relation to physico-chemical parameters in a tropical reservoir of the River Ganga basin, India - Jeetendra Kumar; Absar Alam; Uttam Kumar Sarkar; Basanta Kumar Das; Vijay Kumar; Saket Kumar Srivastava (Sustainable Water Resources Management, 2020)

Food and Feeding Ecology of the Non-native Nile Tilapia Oreochromis niloticus (Linnaeus, 1758) in the River Yamuna, India - Absar Alam; N. K. Chadha; K. D. Joshi; S. K. Chakraborty; Paramita Banerjee Sawant; Tarkeshwar Kumar; Kalpana Srivastava; S. C. S. Das; A. P. Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Adjustments of serum lactate dehydrogenase isoenzymes and their significance in monitoring the treatment in patients with tubercular pyothorax - Riaz Ahmad; Mumtaz Alam; M. Faisal Siddiqui; Absar-ul Hasnain (Indian Journal of Clinical Biochemistry, 2008)